The influence of literacy and numeracy learning in IPS subjects on students' 21st-century skills - Fathurahman, Muhamad Farhan; Qodariah, Lelly; Gunawan, Rudy (Program Pascasarjana Universitas Negeri Yogyakarta, 2023)
This research contributes to describing the effect of literacy and numeracy learning on social studies subjects in schools and looks at how it affects 21st-century skills. This research was conducted at SMP Negeri 2 Cikupa. Based on existing theories, it is known that this research hypothesizes that learning literacy and numeracy in social studies subjects can develop students' 21st-century skills. This study used a population of all SMP Negeri 2 Cikupa, which amounted to 1165 students in grades 7, 8, and 9. The samples used just two classes of 9G and 9H classes. The sample was selected through simple random sampling because the population is included in the homogeneous category. The method used is quantitative, with the independent variable X1 literacy, X2 numeracy, and the dependent variable Y1 21st century skills. The data analysis technique was carried out by dividing the research subjects into the experimental and control classes, each being tested with a pretest, posttest, data prerequisites, hypothesis testing T, F, and determinant coefficients. This study concludes that the literacy variable, numeracy, influences 21st-century skills, as evidenced by the results of the literacy T-test on 21st-century skills, which shows that t count 4.676 > t table 2.042 and sig. 0.000 < 0.05 and numeration on 21st century skills t count 3,527 > t table 2.042 and sig. 0.001 < 0.05.